Measurement and Quantification of Caking in Powders. (2015) - Freeman, Tim; Brockbank, Katrina; Armstrong, Brian
Abstract: Significant numbers of materials in the food, chemical and pharmaceutical industries, from raw feeds, additives and intermediates through to manufactured products, are sold as free-flowing, easily processable powders. However, for logistical reasons, these materials are often stored for extended periods during processing and some will gain strength during such storage periods due to particle/particle interaction. This is generally referred to as 'caking' and can significantly limit the ability of a powder to pass uninterrupted through the process and can detrimentally impact product quality. This paper will evaluate the change flow properties of powders subjected to moisture. It will show how the propensity to cake can be effectively quantified with respect to the powders' flow properties and how this can assist with understanding and adapting the processing environment to retain optimal processability. Moreover it will show how in some cases caking is not a homogeneous progression and how such non-homogeneity can be evaluated and quantified.